Veterans Justice Programs: Assessing Population Risks for Suicide Deaths and Attempts. Issue 4 (9th March 2020) - Palframan, Kristen M.; Blue‐Howells, Jessica; Clark, Sean C.; McCarthy, John F.
Abstract : Objectives: Understanding suicide risks among Veteran subpopulations is a national priority. This study assessed risks of suicide, suicide attempts, and other‐cause mortality among recipients of Veterans Health Administration (VHA) Veterans Justice Program services as compared to other Veteran VHA users. Methods: Per VHA records, the cohort included 5, 401, 192 Veterans alive as of January 1, 2013 and with VHA utilization in 2012. Receipt of Veterans Justice Outreach (VJO) or Health Care for Reentry Veterans (HCRV) services in 2012 was assessed using encounter codes. Multivariable proportional hazards regression assessed risks of suicide (per National Death Index search results from the VA/DoD Mortality Data Repository) and attempts (per diagnoses and site reports) in 2013–2016, adjusting for demographic and clinical indicators. Results: Compared to other patients, Veterans with VJO encounters had greater risk of suicide (unadjusted HR = 2.80, 95% confidence interval [CI] = 2.30–3.40; adjusted HR = 1.25, 95% CI = 1.02–1.53) and attempts (unadjusted HR = 8.88, 95% CI = 8.45–9.35; adjusted HR = 1.06, 95% CI = 1.00–1.11). Veterans with HCRV encounters had elevated risk of suicide attempts (unadjusted HR = 4.56, 95% CI = 4.00–5.20; adjusted HR = 1.42, 95% CI = 1.24–1.62). Risks were also elevated for other external causes of mortality. Conclusions: Findings document increased risk of suicidal behavior among Veterans Justice Program recipients. These results have informed VHA suicide prevention activities.